2017
DOI: 10.1507/endocrj.ej16-0619
|View full text |Cite
|
Sign up to set email alerts
|

A higher score on the Aging Males’ Symptoms scale is associated with insulin resistance in middle-aged men

Abstract: DECREASED ANDROGEN LEVELS associated with aging cause various symptoms, termed late-onset hypogonadism (LOH) [1][2][3]. LOH is characterized by (i) somatovegetative symptoms and conditions, including weakness, fatigue, sleep disturbance, visceral obesity, sarcopenia and osteopenia (or osteoporosis), (ii) psychological symptoms, including disturbed sense of well-being, depressed mood, irritability and anxiety and (iii) sexual symptoms, including decreased libido and erectile dysfunction.Visceral obesity has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…However, in our study, no significant association between FT and SDS or AMS scale was found. Since our results together with results of previous studies suggest that SDS or AMS scale has a poor degree of specificity, these scales alone are not ideal tools for screening latent conditions of testosterone deficiency [15][16][17].…”
Section: Discussioncontrasting
confidence: 50%
“…However, in our study, no significant association between FT and SDS or AMS scale was found. Since our results together with results of previous studies suggest that SDS or AMS scale has a poor degree of specificity, these scales alone are not ideal tools for screening latent conditions of testosterone deficiency [15][16][17].…”
Section: Discussioncontrasting
confidence: 50%
“…Only the psychological symptom score of the AMS scores was reported to be associated with serum T concentration in men aged 45-60 years who were employed as manual workers by the Vienna Municipality [10]. In our previous study, no significant association was identified between total AMS score and T concentration, and only the sexual subscale scores were significantly inversely associated with FT or calculated bioavailable testosterone (cBT) [4].…”
mentioning
confidence: 83%
“…the effects of testosterone (T) replacement therapy on quality of life [2]. However, previous studies, including our own, have found no correlation between the AMS and serum T concentration [2][3][4]. Furthermore, the AMS scale was shown not to be an effective means of identifying T deficiency, because of its low specificity [5].…”
mentioning
confidence: 86%
See 2 more Smart Citations